ORAL MUCOSAL BURN CAUSED BY THE TOPICAL APPLICATION OF A CLOVE OIL CONCENTRATE - Sutrania Dewi Sulaksana; Anandina Irmagita Soegyanto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Clove is an herb that has been known for centuries as natural remedy and food preservatives. Despite its several important biological activities such as antioxidant activity, antimicrobial, antinociceptive, and antiviral effects, clove’s end product can cause some tissue reaction that varies from low-grade local to serious reactions such as anaphylactic reaction. This case report aim to discuss on clove oil extract effect when applied topically to oral mucosal.Case Presentation: A 30-year-old female came to Oral Medicine Clinic of Universitas Indonesia Dental Hospital, with complaint of painful multiple mouth ulceration since 3 weeks earlier that got worsen in the past 2 days after clove oil extract topical application. She had a history of canker sore in every 2 months since her adolescence. Extra oral examination showed desquamation and brown crust on lips. Intraoral examination revealed multiple, shallow, irregular ulcers, surrounded by diffuse erythema, on buccal mucosa, soft palate, anterior dorsum of the tongue, and lower anterior muco buccal fold. Subjective and clinical examination were consistent with oral mucosal burn and the patient was instructed to discontinue clove oil usage, while prescribed with Chlorhexidine Gluconate 0,2% mouthwash and Vaseline album.Conclusion: The increasing practice of herbal medicine, such as cloves products, should raise our awareness since when used inappropriately, it could cause oral mucosal burn. In the management of these cases, dentist must perform thorough anamnesis and examination to establish accurate diagnosis and plan proper treatment.